Failing the System? Enfocing the Right to Education in New Zealand - Ryan, E J (Victoria University of Wellington Law Review, 2004)
At both the international and domestic level, the existence of a right to education is given widespread support. But what are the content and consequences of this right? The meaning of the right to education was examined recently in the context of special education by the High Court and Court of Appeal in Daniels v Attorney-General. The High Court saw the right as a substantive one; the Court of Appeal viewed it in procedural terms. These different conceptions of the right affected the remedies available to the plaintiffs. This article assesses the competing understandings of the education right in NZ, and concludes, particularly in light of the House of Lords' decision in Phelps v Hillingdon London Borough Council, that the High Court's approach is to be preferred.